2008
DOI: 10.1021/jf8001679
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Oil Content and of Major Fatty Acid Composition in Almond (Prunus amygdalus Batsch) and Its Relationship with Kernel Quality

Abstract: Oil content and fatty acid composition were determined for two years in the kernel oil of eight cultivars and 47 advanced self-compatible almond genotypes developed in an almond breeding program. Considerable variation between genotypes was found for all parameters. Oil content ranged from 48% to 67% of the total kernel dry weight but was consistent over the two years. Fatty acid composition was also very variable, with significant differences between genotypes, even in genotypes of the same progeny. Oleic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
106
3
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(135 citation statements)
references
References 21 publications
21
106
3
5
Order By: Relevance
“…In addition, they indicated that this rate can be used as distinction of genotypes because this rate does not change over the years and linoleic acid is less stable and less saturated than oleic acid. In our study, the oleic acid ratio was found to be 64.05-80.68% and the linoleic acid ratio was found to be 12.65-27.00%, similar to [13] results. Previous studies [24,27] indicated that synthesis of fatty acids may vary according to genetic, ecological, morphological, physiological and cultura factors.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…In addition, they indicated that this rate can be used as distinction of genotypes because this rate does not change over the years and linoleic acid is less stable and less saturated than oleic acid. In our study, the oleic acid ratio was found to be 64.05-80.68% and the linoleic acid ratio was found to be 12.65-27.00%, similar to [13] results. Previous studies [24,27] indicated that synthesis of fatty acids may vary according to genetic, ecological, morphological, physiological and cultura factors.…”
Section: Resultssupporting
confidence: 90%
“…In this study, in general, a large number of genotypes and more comprehensive fatty acid compositions of almond genotypes were studied. Our findings were found to be similar to [26] and especially [13] results. Kodad and Socias [13] showed that genotypes' oleic/linoleic acid ratio is an important factor in determining the stability of almond oil.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations